Experiencias de danzaterapia de mujeres que han sufrido cáncer de mama. Un estudio fenomenológico - Forte Lopes, Vanessa Fernanda; Bueno Neme, Carmen Maria (Psicooncología, 2016)
Objective: This essay aims at identifying, describing and analyzing possible changes both in the experience of the body and in interpersonal relations of women with breast cancer, which result from their participation in Dance Therapy group meetings. Method: This is a phenomenologically oriented qualitative research using Maria Fux´s dance therapy method for group experiences. Eight meetings are described here, and an analysis of descriptions based primarily on Merleau-Ponty and María Fux is provided. Results: The participants have been able to express pain and sorrow over the circumstances that breast cancer and its relational environments have brought to their lives. They have been able to go through moments of creation and surrender to the rhythmic body sensations and experiential environment with different emotions lived separately and jointly. They have revived memories and sensations of their childhood and adolescence, and finally, they have rediscovered their sensitive body through body resignifications marked by the absence of the breast, and by means of feelings of greater acceptance and integration of lived experiences in new gestalts. Conclusions: This project is still under way, but it is already possible to conclude that the life experiences provided in dance therapy have allowed these women to improve their integration and welfare. Likewise, they have felt positive changes in the perception of their corporality and in their way of being in the world and with other subjects, thus experiencing the body in a new and different way.